IgA Enhances IGF-1 Mitogenic Activity Via Receptor Modulation in Glomerular Mesangial Cells: Implications for IgA-Induced Nephropathy - Amal Al-Eisa; Gursev S. Dhaunsi (Kidney & Blood Pressure Research, 2017)
Background/Aim: Glomerulonephritis due to mesangial proliferation is responsible for renal dysfunction in IgA nephropathy (IgAN), however molecular mechanisms of pathogenesis are not well known. We examined the effect of IgA on Insulin-like Growth Factor-1 (IGF-1) activity, a potent mitogen with vital role in growth and development of children, and IGF-1 receptor (IGF-1R) in cultures of glomerular mesangial cells (GMC). Methods: GMC were isolated from rat kidneys using sieving and enzymatic digestion of tissue homogenates, and cultured in RPMI 1640 medium. GMC cultures were treated with IgA (0-10 µg/ml) in the presence or absence of IGF-1 and fetal bovine serum (FBS), and BrdU incorporation was measured. IGF-1 levels were assayed along with real-time PCR quantification of IGF-1R mRNA. Results: Treatment of GMC with IgA (5 -10 µg/ml) significantly (p < 0.01) increased the BrdU incorporation in the presence or absence of FBS or IGF-1. IgA-mediated effects were more pronounced in IGF-1 treated cells that were significantly (p < 0.01) blocked by pretreatment of cells with IGF-1 receptor antibody or genistein. IgA significantly increased the levels of IGF-1 in culture supernatants and GMC homogenates. IGF-1R mRNA was significantly (p < 0.01) increased in IgA treated cells particularly by co-treatment with IGF-1. Conclusion: These findings show that IgA enhances the IGF-1 activity in GMC via stimulation of IGF-1R gene transcription and suggest a role for IGF-1 in pathogenesis of IgAN.